Determinanten der Wettbewerbsfähigkeit ,,erweiterter Familienbetriebe“: Ergebnisse einer Betriebsleiterbefragung; Determinants of Competitiveness of "Extended Family Farms" - Empirical Results from a Survey of Farm Managers - Christian Schaper; Mark Deimel; Ludwig Theuvsen (German Journal of Agricultural Economics (GJAE), 2011)
– Due to an intensifying competition, gaining and sustaining competitive advantages have become increasingly important for family farms in recent years. In the course of general structural changes in agriculture, so-called "extended family farms" have emerged as a predominant form of farming businesses in many, mainly western parts of Germany. Through combining traditional family-labour-based governance structures with additional non-family labour, extended family farms can realize economies of scale. Thus, they are often considered a sustainable type of organisation that is able to cope with international competition. So far existing research has not fully explored the factors determining the competitiveness of extended family farms. Against this background, this article analyzes potential determinants of competitiveness of extended family farms on the basis of a survey of 103 farm managers. The empirical results show that the success of the farms surveyed is not only based on the realization of technical economies of scale, but also on the personality of the farm managers and the strategies implemented.
Keywords: 330; Familienunternehmen; Wettbewerb; Wirtschaftliche Anpassung; Westdeutsche Bundesländer